Infrared Observations of Ganymede From the Jovian InfraRed Auroral Mapper on Juno. Issue 12 (15th December 2020) - Mura, A.; Adriani, A.; Sordini, R.; Sindoni, G.; Plainaki, C.; Tosi, F.; Filacchione, G.; Bolton, S.; Zambon, F.; Hansen, C. J.; Ciarniello, M.; Brooks, S.; et al.
Abstract: The Jovian InfraRed Auroral Mapper (JIRAM) on board the NASA Juno spacecraft is a dual‐band imager and spectrometer in the 2–5 μm range with 9‐nm spectral sampling, primarily designed to study the Jovian atmosphere and aurorae. In addition to these goals, JIRAM is used to obtain images and spectra of the Galilean satellites, every time the spacecraft attitude is favorable. Here we present JIRAM images and spectra of Ganymede obtained during the first 4 years of the mission. In particular, on 26 December 2019, during a relatively close passage of Juno with the moon, a dedicated reorientation of the spacecraft was performed to achieve optimized observations of Ganymede by Juno's remote sensing instruments, including JIRAM. In the outbound phase of the flyby, observing the northern polar regions of Ganymede at a distance of roughly 100, 000 km, JIRAM collected infrared images and spectra of the surface at a spatial resolution as high as 23 km per pixel, covering high northern latitudes that were scarcely mapped previously. A photometric model of Ganymede reflectance is produced, which diverges from the Lambert model. The spatial distribution of the obtained spectra complements the available coverage of the surface, with particular regard to the 2.0‐µm water ice absorption band and, to a lesser extent, to the 4.26‐µm spectral feature diagnostic of CO2 trapped in water ice. The water ice distribution is compatible with sputtered‐induced water ice grain enrichment at high latitude (>45°). Several minor species (hydrated salts, trapped H2, CO2, and acids) are also identified in the measured spectra. Plain Language Summary: The Jovian Infrared Auroral Mapper (JIRAM) is a dual‐band imager and spectrometer on the NASA Juno spacecraft. It works in the range of 2–5 μm and its spectral sampling is 9 nm. JIRAM is mainly used to study the Jovian atmosphere and aurora. JIRAM is also used to obtain images and spectra of the moons of Jupiter, every time the spacecraft has a favorable attitude. Here, we show Ganymede images and spectra obtained during the first 4 years of the mission. On 26 December 2019, during a close passage of Juno to Ganymede, JIRAM observed it at a distance of approximately 100, 000 km. In this occasion, JIRAM collected infrared images and surface spectra with a spatial resolution of up to 23 km per pixel. This data covers North polar regions that were not mapped before. A photometric model of Ganymede's reflectance was produced, and it is different from the Lambert model. The spatial distribution of the obtained spectrum can supplement the available coverage of the surface, especially for the 2.0 µm water ice absorption band. At high latitudes (>45°), the distribution of water ice is compatible with the enrichment of water ice particles induced by sputtering. Several minor species (hydrated salts, trapped H2, CO2, and acids) were also identified in the measured spectra. Key Points: Water ice distribution for previously unmapped regions Latitudinal variability of CO2 spectral feature New photometric model for Ganymede reflectance